Anathematizing Barthes and Admiring Beckett with Eugène Ionesco. Issue 2 (July 2022) - Ionescu, Arleen
Abstract : This article explores the world of theatre from within and beyond the stage and brings together Roland Barthes as a critic and Samuel Beckett as a playwright via a third character, the Romanian-born playwright Eugène Ionesco, who anathematized the former and admired the latter. The article starts from Martin Esslin's The Theatre of the Absurd (1961), which defined Beckett's and Ionesco's art, pointing out that whilst Esslin showed why their works produced 'bewilderment' in England and the US, he ignored the Paris debates of the 1950s to early 1960s. It then covers the intricate history of Barthes's polemical articles on avant-garde theatre and focuses on Barthes hailing Bertolt Brecht as an innovator who redefined theatre as belonging to a community. The next section engages with Beckett's and Ionesco's ideas on staging and their relation to Brecht and the Brechtians. The epilogue proposes a reading of Ionesco's satirical play Improvisation or the Shepherd's Chameleon (1955), which features Barthes and two other representatives of nouvelle critique as characters.